2009
DOI: 10.1001/archneurol.2009.20
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Primary Generalized Dystonia

Abstract: Background: Pallidal deep brain stimulation (DBS) is the best therapeutic option for patients with disabling primary generalized dystonia (PGD) that is refractory to medications. However, little is known about its long-term effects.Objective: To describe long-term clinical outcomes in patients with PGD who underwent pallidal DBS.Design: Case series.Setting: University hospital.Patients: Thirty consecutive patients with at least 2 years' follow-up after pallidal DBS for intractable PGD.Interventions: Pallidal D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
107
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 21 publications
(49 reference statements)
13
107
1
2
Order By: Relevance
“…23 The disorder is more common in females by a 3:1 ratio. 14 Medical treatment of this condition has generally been unsuccessful and often limited by partial response and adverse side effects. Stereotactic surgical ablation techniques had been used for several years with mixed results.…”
mentioning
confidence: 99%
“…23 The disorder is more common in females by a 3:1 ratio. 14 Medical treatment of this condition has generally been unsuccessful and often limited by partial response and adverse side effects. Stereotactic surgical ablation techniques had been used for several years with mixed results.…”
mentioning
confidence: 99%
“…Fixed skeletal deformity, longer disease duration at surgery, older age at surgery, and more severe motor symptoms at surgery have been associated with a poor outcome (Andrews et al, 2010;Isaias et al, 2008Isaias et al, , 2011. Speech and swallowing symptoms are less responsive than axial or limb dystonia (Isaias et al, 2009;Vidailhet et al, 2007), even within an individual patient.…”
Section: Primary Generalized Dystoniamentioning
confidence: 95%
“…The mean improvement in the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) movement score was 46% at 6 months in one study (Kupsch et al, 2006) and 51% at 1 year and 58% at 3 year in another study without permanent adverse effects (Vidailhet et al, 2005(Vidailhet et al, , 2007. A recent long-term follow-up study showed that improvement by GPi DBS was sustained for up to 8 years (Isaias et al, 2009). Although results from early studies suggested that patients positive for DYT1 mutation have a greater benefit (Coubes et al, 2000;Krauss et al, 2003), it is now widely accepted that there is no difference in the outcome between DYT1-posivie and DYT1-negative patients (Isaias et al, 2008(Isaias et al, , 2011Kupsch et al, 2006;Vidailhet et al, 2005).…”
Section: Primary Generalized Dystoniamentioning
confidence: 96%
“…GPi DBS has been established as an effective surgical treatment alternative for primary dystonia, with a 50-80% motor benefit according to short-term [53,54] and long-term longitudinal studies [55,56,57,58]. In a randomized controlled trial by Kupsch et al [53], 40 patients with primary dystonia were randomly assigned to either bilateral GPi DBS or sham stimulation (in which the device was implanted but not activated) for 3 months; thereafter, all patients completed 6 months of DBS therapy and were followed annually with a 5-year follow-up period [53,58].…”
Section: Clinical Applications Of Deep Brain Stimulationmentioning
confidence: 99%
“…One similar controlled trial demonstrated that DBS provided sustained motor benefit after 3 years, with BFMDRS-M score improved by 51% at 1 year and still maintained at 3 years (58%); in addition, mild long-term improvements in quality of life and attention were also observed [54,57]. Another study of 23 patients reported that BFMDRS-M scores improved by 79.6% at 1 year and by 82.5% at 2 years, and these scores were maintained for up to 8 years postoperatively [55]. A retrospective study involving 44 patients drawn from five experienced DBS centers also showed BFMDRS improvement with DBS treatment, with 74.9% at 1 year and 82.6% at 3 years [56].…”
Section: Clinical Applications Of Deep Brain Stimulationmentioning
confidence: 99%